Programmatic actions in oral health: coping with social inequities - Efigênia Ferreira e Ferreira; Nilce Emy Tomita; Gisele da Silva Dalben (Sociedade Brasileira de Pesquisa Odontológica, 2012)
Inequities are health imbalances that are avoidable, unfair and unnecessary. Studies on health inequities address the need for emergency care related to oral-dental lesions from external causes, toothache or prevalence of oral lesions, taking into account the differences between individuals and/or populations in terms of risk conditions to acquiring disease or access to health services. Inequities may be caused by the health service itself, because diseases affect socially deprived individuals more frequently and severely, especially because of multimorbidity. In the current Brazilian public health situation, programmatic actions are based on technological knowledge, especially epidemiology, focused on specific pathologies or disease risk groups, and relate closely to the organization of programmed demand. Moreover, programmatic actions should strategically use technological devices, without disregarding technical and policy flexibility, and should be closely related to inter-subjectivity and ethics, in order to develop emancipating capabilities. An action having this structure could make it easier to achieve Universality, Equity and Integrality.